Examining the effect of board size on credit risk of universal banks in Ghana - Emmanuel Debrah; Alexander Preko; Seth Ampadu (Cogent Business & Management, 2022)
This study examines the effect of board size on credit risk with bank ownership, bank size and bank age acting as controls for the first time in the Ghanaian Banking Sector. Using Quantile Regression modelling, data was obtained from 12 universal Banks in Ghana over the period from 2011 to 2018 for the study. Agency theory was used since conflicts that exist between managers and shareholders need to be mitigated via the use of suitable corporate governance mechanism in the form of board size. The findings revealed that a universal bank with a small board size is not likely to reduce credit risk. Thus, the study established the importance of having large boards which are independent of management of universal banks in Ghana: large boards may enhance credit assessment and monitoring thereby reducing credit risk. The study used only quantitative techniques; however, using qualitative method in addition to the quantitative approach might enhance the understanding of the effect of board size on credit risk of universal banks in Ghana. Besides, the study relied on secondary data, though it is empirically established that there are biases inherent in such data.
Keywords: 650; Agency Theory; Board Size; Credit Risk; Quantile Regression; Universal Banks